The matching skill of educational counselors (Journal of the College of Basic Education, 2023)
The research aimed to identify the matching skill of educational counselors, and the significance of the difference in the matching skill of educational counselors according to the gender variable (male/female), and the significance of the difference in the matching skill of educational counselors according to the service variable (1-5 years) (6 years-and more). In order to achieve the objectives of the research, the researcher adopted the congruence skill scale that he prepared according to Rogers' theory, and the scale consisted of (25) items, and its characteristics were confirmed, as the scale was applied to a sample of (100) with (50) male (50) female male guides, who were chosen randomly Cluster, and the results of the research showed that the individuals of the research sample possess the matching skill according to the hypothetical medium, and there are statistically significant differences in the matching skill according to the gender variable in favor of females, and there are no statistically significant differences in the matching skill according to the service variable (1-5 years) (6 years or more). ). In light of the results, the researcher presented a number of recommendations and proposals for research.Keywords: matching skill - psychological counseling - counsellors